Persepsi Mahasiswa Terhadap Penerapan Metode Resitasi Pada Pembelajaran Daring di Universitas Nahdlatul Ulama Indonesia - Sri Wahyuni (Universitas Pancasakti Tegal, 2021)
The recitation method is one of the learning methods which is an alternative to educators to keep his students involvedactively in the online learning activities process. To applay that method, in order to achieve optimal results and not aburden to the students, be required perceptions from the students as a control to take policy. This research is meant toknow student’s perceptions toward the application method of recitation and its benefits of the online learning atNahdaltul Ulama University who were 62 students. The research population were sixth semester students of the Islamicreligious education program at Nahdlatul Ulama Indonesia University. The sample used was just students beingtaught by researcher using recitation method as method of learning. The result of research indicate that PAI studentgave positive perceptions toward applaying recitation method on online learning 88,17%, and the perception towardbenefits from applying recitation method 96,37%. So it can be concluded that the recitation method relevant is used inonline learning and gave benefits that have positive impact to the quality of student’s learning.